2012
DOI: 10.1016/j.jcf.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) in Chinese patients with congenital bilateral absence of vas deferens

Abstract: Most patients with CBAVD have mutations in the CFTR gene. A mild genotype with one or two mild or variable mutations was observed in all the patients. These findings improve our understanding of the distribution of CFTR alleles in CBAVD patients and will facilitate the development of more sensitive CFTR mutation screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 39 publications
3
22
1
Order By: Relevance
“…[6][7][8]11 Furthermore, some studies from China reported that most patients with congenital bilateral absence of vas deferens, which is also a CFTR-related disorder, had a different CFTR mutation spectrum compared to that of Caucasian patients. [23][24][25][26] These results further support the concept that the spectrum of CFTR mutations in Chinese is highly specific for the Chinese population.…”
Section: Discussionsupporting
confidence: 76%
“…[6][7][8]11 Furthermore, some studies from China reported that most patients with congenital bilateral absence of vas deferens, which is also a CFTR-related disorder, had a different CFTR mutation spectrum compared to that of Caucasian patients. [23][24][25][26] These results further support the concept that the spectrum of CFTR mutations in Chinese is highly specific for the Chinese population.…”
Section: Discussionsupporting
confidence: 76%
“…Among the six Gulf Cooperation Council (GCC) countries (Bahrain, Kuwait, Oman, Qatar, Saudi Arabia and UAE), the mutations L578delTA and c.1069G>A were first reported as novel mutations in Oman; however, the latter has also been reported in the Chinese population . These two mutations result in typical clinical CF phenotypes, including pancreatic insufficiency, poor lung function and chronic Pseudomonas colonization (Table S1, Supplementary Information) .…”
Section: Resultsmentioning
confidence: 99%
“…CFTR gene analyses have focused primarily on the intron 8 polymorphism, poly-T (IVS8 poly-T), as well as TG-repeats, and the M470V allele. However, only 4 studies have been performed to investigate the poly-T polymorphism and congenital bilateral absence of the vas deferens in Chinese patients [1417]. …”
Section: Discussionmentioning
confidence: 99%